Role of poly-ADP-ribose polymerase inhibitors after brain progression in platinum-sensitive ovarian cancer: a case report and review of the literature - Lendinez-Sanchez, Gonzalo; Diaz-Redondo, Tamara; Iglesias-Campos, Marcos; Garrido-Almazán, Lucía; Alba-Conejo, Emilio; Rueda-Dominguez, Antonio; Sanchez-Muñoz, Alfonso (Frontiers in Oncology, 2024)
Introduction: The incidence of brain metastases in ovarian cancer is rare, about 1-2%. Retrospective studies show patients with BRCA 1/2 mutations have a higher risk. The trimodal approach of surgery, radiotherapy, and chemotherapy yields better outcomes, but prognosis remains poor with overall survival around 1 year. Poly-ADP-ribose-polymerase-inhibitors (PARPi) offer a new alternative for managing advanced ovarian cancer. The SOLO2, NOVA, and ARIEL3 clinical trials lack data on patients with brain metastases; published evidence for PARPi in this context comes only from case reports and retrospective studies. Case report: We present a 54-year-old woman with stage IV ovarian high-grade serous papillary carcinoma who, after 37 months of olaparib treatment, developed a single brain lesion. Post radical treatment with surgery and whole brain radiotherapy, she resumed olaparib with no disease evidence for 15 months. After a second brain relapse treated with stereotactic radiosurgery, the patient continued olaparib beyond brain progression with no extracranial disease. Despite no changes in brain lesion size or number, her neurological condition worsened, and she died 8 months after the second progression. Discussion: The higher incidence of brain metastases in ovarian cancer suggests possible CNS tropism in BRCA mutated patients. Preclinical studies show PARPi can cross the blood-brain barrier, potentially offering antitumor activity in the CNS while controlling extracranial disease. Best survival outcomes are seen with a trimodal approach; adding PARPi could improve survival in platinum-sensitive disease. Targeted therapies combined with local treatments in other malignancies suggest potential effectiveness due to tumor heterogeneity. PARPi before brain metastasis may delay its diagnosis; using PARPi after brain metastases could improve outcomes. Conclusion: The role of PARPi in treating ovarian cancer brain metastases requires more studies. In the context of radical brain metastasis treatment, with no extracranial disease, continuing PARPi beyond brain progression should be considered.